A modular activity to support knowledge retention, application, and metacognition in undergraduate immunology - Lisa M. D'Ambrosio (Journal of Microbiology & Biology Education)
ABSTRACT Learning in undergraduate immunology requires students to be able to retain knowledge, to apply information to new contexts, and to self-assess their understanding of concepts. These core competencies strengthen students’ critical thinking and metacognitive skills which, in turn, enhances their ability to identify knowledge gaps and strategies to support future learning. Retrieval practice and feedback-driven metacognition are evidence-based teaching strategies that have been demonstrated to enhance knowledge retention and metacognition in a range of academic disciplines and levels of education, although their implementation and impact on learning in undergraduate immunology remain largely unexplored. To this end, I designed a modular “practice session” activity for a 12-week, upper-level, undergraduate immunology course that incorporates periodic retrieval practice and feedback-driven metacognition to support students’ knowledge retention, application of information, and metacognitive skills. Near the end of the course, a survey was conducted to assess student perceptions on whether the activity supported learning and metacognition in immunology. Instructional resources are provided to facilitate easy adaptation of this modular activity to courses of diverse science disciplines and levels of study in higher education.